2022
DOI: 10.1007/s00248-022-02126-1
|View full text |Cite
|
Sign up to set email alerts
|

First Study Case of Microbial Biocontrol Agents Isolated from Aquaponics Through the Mining of High-Throughput Sequencing Data to Control Pythium aphanidermatum on Lettuce

Abstract: Aquaponics is defined as a sustainable and integrated system that combines fish aquaculture and hydroponic plant production in the same recirculated water loop. A recent study using high-throughput sequencing (HTS) technologies highlighted that microbial communities from an aquaponic system could control one of the most problematic pathogens in soilless lettuce culture, namely, Pythium aphanidermatum. Therefore, this study aims at isolating the microorganisms responsible for this biocontrol action. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Although as effective as Cf and Cap, combination of G2 with C13 and/or SHb30 (both bacterial strains) did not bring significant additional effect. In relation to Stouvenakers et al (2023), these results showed that antagonistic activity of G2 is reproducible over time. Studies on A. flavus use against P. aphanidermatum are scarce and limited to few papers (Shanmugan and Sakurana Varma, 1999;Stouvenakers et al, 2023), while atoxigenic strains were intensively studied to control aflatoxin in cereal crops (Khan et al, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Although as effective as Cf and Cap, combination of G2 with C13 and/or SHb30 (both bacterial strains) did not bring significant additional effect. In relation to Stouvenakers et al (2023), these results showed that antagonistic activity of G2 is reproducible over time. Studies on A. flavus use against P. aphanidermatum are scarce and limited to few papers (Shanmugan and Sakurana Varma, 1999;Stouvenakers et al, 2023), while atoxigenic strains were intensively studied to control aflatoxin in cereal crops (Khan et al, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 79%
“…Biocontrol experiment of P. aphanidermatum disease on lettuce seedlings was conducted as described in Stouvenakers et al (2023). Organic pelleted lettuce seeds (Lactuca sativa 'Lucrecia RZ') (Rijk Zwaan, Merksem, Belgium) were sown in 25×25×40 mm rockwool plugs (Grodan B.V., Roermond, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations